Cost‐effectiveness and cost–utility of endovascular versus open repair of ruptured abdominal aortic aneurysm in the Amsterdam Acute Aneurysm Trial. Issue 3 (February 2014) - Kapma, M. R.; Dijksman, L. M.; Reimerink, J. J.; de Groof, A. J.; Zeebregts, C. J.; Wisselink, W.; Balm, R.; Dijkgraaf, M. G. W.; Vahl, A. C.
<x xml:space="preserve">Abstract</x> Background Minimally invasive endovascular aneurysm repair (EVAR) could be a surgical technique that improves outcome of patients with ruptured abdominal aortic aneurysm (rAAA). The aim of this study was to analyse the cost‐effectiveness and cost–utility of EVAR compared with standard open repair (OR) in the treatment of rAAA, with costs per 30‐day and 6‐month survivor as outcome parameters. Methods Resource use was determined from the Amsterdam Acute Aneurysm (AJAX) trial, a multicentre randomized trial comparing EVAR with OR in patients with rAAA. The analysis was performed from a provider perspective. All costs were calculated as if all patients had been treated in the same hospital (Onze Lieve Vrouwe Gasthuis, teaching hospital). Results A total of 116 patients were randomized. The 30‐day mortality rate was 21 per cent after EVAR and 25 per cent for OR: absolute risk reduction (ARR) 4·4 (95 per cent confidence interval (c.i.) –11·0 to 19·7) per cent. At 6 months, the total mortality rate for EVAR was 28 per cent, compared with 31 per cent among those assigned to OR: ARR 2·4 (−14·2 to 19·0) per cent. The mean cost difference between EVAR and OR was €5306 (95 per cent c.i. –1854 to 12 659) at 30 days and €10 189 (−2477 to 24 506) at 6 months. The incremental cost‐effectiveness ratio per prevented death was €120 591 at 30 days and €424 542 at 6 months. There was no significant difference in quality of life between EVAR and OR. Nor was EVAR superior regarding cost–utility. Conclusion EVAR may be more effective for rAAA, but its increased costs mean that it is unaffordable based on current standards of societal willingness‐to‐pay for health gains.